Higher order risk attitudes: a review of experimental evidence - Trautmann, Stefan T.; Kuilen, Gijs van de (European economic review, 2018)
This paper reviews the recent, but fast-growing experimental literature on higher order risk attitudes. After introducing the theoretical context, we first review the basic evidence and empirical moderators of these risk attitudes. We then discuss recent extensions to ambiguity, time risk, and multi-attribute utility. In the last part we review indirect evidence from applied economic decision tasks.
Gesehen am 10.05.2019